2011
DOI: 10.1038/sc.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Expected spinal cord independence measure, third version, scores for various neurological levels after complete spinal cord lesions

Abstract: 15Rovisco Pais Spinal Centre, Lisbon, Portugal Study design: Multicenter international cohort study. Objective: The objective of this study was to establish target values for Spinal Cord Independence Measure (SCIM) III scoring in rehabilitation for clinically complete spinal cord lesion (SCL) neurological levels. Setting: In total, 13 spinal cord units in six countries from North America, Europe and the Middle East were taken. Methods: Total SCIM III scores and gain at discharge from rehabilitation were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 4 publications
6
27
1
Order By: Relevance
“…For all neurological levels, median score gains for stair management and ground-to-wheelchair transfers were zero. Maximum observed final scores for specific neurological levels are compared with final outcomes following classic inpatient rehabilitation 4 and presented in Table 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all neurological levels, median score gains for stair management and ground-to-wheelchair transfers were zero. Maximum observed final scores for specific neurological levels are compared with final outcomes following classic inpatient rehabilitation 4 and presented in Table 6.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Studies highlight the benefits of significant cost reductions and continued high-quality care by using a combination of inpatient and outpatient programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three large-scale adult studies [3][4][5] established moderate-tostrong reliability and validity and showed that when compared with the FIM (Functional Independence Measure) the SCIM-III had broader content range and was more responsive to change. Additional work has examined clinically important differences in SCIM-III scores, 6 established target values for neurological levels in complete SCI 7 and has validated a self-report version. 8 The self-report version offers a practical alternative to the performance-based version, especially in community-based centers and for longitudinal monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…To move around I use a wheelchair to move around and A. I need total assistance [0] A. I always need help to move my wheelchair [0] B. I need an electric wheelchair or partial assistance to operate a manual wheelchair [1] B. I need a power wheelchair or some help to move my manual wheelchair [1] C. I am independent in a manual wheelchair [2] C. I do not need a power wheelchair and I do not need help to move my manual wheelchair [2] I walk moderate distances and I I walk medium distances and D. need supervision while walking (with or without walking aids) [3] D. Someone is always with me [3] E. walk with a walking frame or crutches, swinging forward with both feet at a time [4] E. I walk with a walker or crutches by swinging both legs and feet together [4] F. walk with crutches or two canes, setting one foot before the other [5] F. I walk with a walker or crutches by moving one foot forward at a time [5] G. walk with one cane [6] G. I walk with one crutch [6] H. walk with a leg orthosis(es) only (e.g. leg splint) [7] H. I walk with braces on my legs and do not need a walker or crutches [7] I. walk without walking aids [8] I. I walk with nothing to help me [8] CONFLICT OF INTEREST The authors declare no conflict of interest.…”
mentioning
confidence: 99%